Diagnosis security problems in cloud computing for business cloud - Shakir M.; Abubakar A.B.; Yousoff Y.B.; Sagher A.M.; Alkayali H. (Asian Research Publishing Network, 2023)
Cloud computing is considered as one of the rapid growing technologies for it has high flexibility in both usage and application; therefore, it has been used widely by many organizations. Cloud computing features ease, fast accessibility of the data and cost reduction for data storage. Consequently, a number of organizations are using this technology. Since the cloud computing has been used widely in various parts of the world by many originations, several security problems in cloud computing exist. This study was carried out by distributing questionnaires to different organizations in selected twelve (12) countries. This paper aims to examine the security problems and to identify the characteristics of such security problems, in addition this study will examine the important issues in security cloud computing and will determine the frames to improve security systems for cloud computing. The findings of this study, firstly the organizations or institutions are very concerned in improving the security of cloud computing through the application of the authority model and dynamic classification of data model based on the multi-level security. Secondly , they prefer to develop the multi-key cipher algorithm in order to manage the encryption based on the level of security. 2005 - 2016 JATIT & LLS. All rights reserved.